Psychiatric reform revisited - CHRISTODOULOU, GEORGE (Masson Italy, 2009)
The trend towards the establishment of community psychiatric services seems to be universal. However, before closing down a mental hospital, it is necessary to establish the appropriate alternative facilities in the community. Every de-institutionalization program should have a diachronic component, and cultural issues should be taken into consideration. Care for each patient has to be decided upon on the basis of the characteristics of that patient. Finally, de-institutionalization is just one aspect of psychiatric reform. Primary psychiatric prevention is equally or even more important